Analysis of Student Difficulties in Online Learning During the COVID-19 Pandemic Class VIII MTsS Khudrinnur In Toari District - Sari, Ika Mustika; Sari, Tri Maniarta; Maretik, Maretik (Journal of Biological Science and Education, 2022)
Learning in schools before the pandemic was carried out directly in schools, but because of the pandemic, it required teachers and students to carry out the online learning process. Teachers and students experience many obstacles in the online learning process, especially for students new to online learning. This study aims to describe students' difficulties in online learning during the Coronavirus disease (COVID-19) pandemic and to find out the causes of students' problems in online learning during the Coronavirus disease (COVID-19) pandemic class VIII Madrasah Tsanawiyah Khudrinnur. This research is a qualitative descriptive study. The samples in this study were students and teachers of class VIII MTsS Khudrinnur. The research instrument is a questionnaire or questionnaire, interviews, and documentation. From the results of the study, it is known that the factors that affect the difficulties in online learning of students are network difficulties of 69.09% of the total number of students. So it can be concluded that the factors that influence students' difficulties in online learning are network difficulties, about 69.09% of the total number of students. Factors do not have a quota of about 68.75 % of the total number of students. The factor of not having a cellphone (HP) is about 66.40% of the total number of students. The aspect of not understanding the material is about 58.85% of the students who do not understand the learning material will ask the teacher when they do not understand. The cool factor for playing games is around 71.35% of students prefer to play games compared to participating in online learning.Â Keywords: Difficulty, Online (Online), MTSS Khudrinnur